Analisis Capital Adequacy Ratio (CAR) Bank Muamalat Indonesia Tahun 2019–2023 - Ramadhani, Nayla Salsabila (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the capital health and financial stability of Bank Muamalat Indonesia for the 2019-2023 period through an analysis of the Capital Adequacy Ratio (CAR). CAR is an important indicator that measures a bank's capital adequacy in bearing risks against its risk-weighted assets (RWA). Data were obtained from the bank's annual report and official OJK publications, then analyzed descriptively longitudinally. The results show that Bank Muamalat's CAR experienced a significant increase from 12.42% in 2019 to 32.70% in 2022, then experienced a moderate decline to 29.42% in 2023. The dramatic increase in 2021-2022 was primarily due to substantial capital injections and the issuance of subordinated instruments, while the decline in 2023 was influenced by asset growth and financing expansion that were faster than capital growth. These findings indicate that although Bank Muamalat is above the regulatory threshold for capital adequacy, the dynamics of expansion and risk pressures still require management and regulatory attention.